Kombinasi Ekstrak Daun Kelor (Moringa oleifera Lamk) Dengan Ekstrak Daun Tin (Ficus carica Linn) Sebagai Larvasida Terhadap Larva Aedes aegypti: Combination of Moringa Leaf Extract (Moringa oleifera Lamk) With Tin Leaf Extract (Ficus carica Linn) As Larvicide Against Aedes aegypti Larvae - Hikma, Selani Rahchian; Ardiansyah, Syahrul (Universitas Muhammadiyah Sidoarjo, 2018)
The use of synthetic larvicides will be resistance of environmental pollution. The Alternatives for deduct negative impact is Moringa leaves and ficus carica Linn leaves as plant larvacides. The content of Moringa leaves and ficus carica Linn leaves is contain secondary metabolites including saponins, flavonoids, alkaloids, and tannins as larvicides. This research aim knowing toxicity combination Moringa leaf extract and ficus carica Linn leaf extract for Aedes aegypti mosquito larvae. This methode using post test only control group design, with five variations of the concentration Moringa leaf extract combination is 100%: 0% tin leaf extract; 25%: 75%; 50%: 50%; 75%: 25%; and 0%: 100% with 4 repetition. The data analysis by univariate and bivariate (kruskal wallis) and mann whitney tests for differences in two samples.m The best result of research is concentration 75%:25% consist death larva time to 10 with total larvae 62%, 25%:75% with total larvae 19%, and increasing for 50%:50% with total larvae 34%.